2007
DOI: 10.1021/la070161h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Copper Hexacyanoferrate Nanoparticles for Building Up Long-Term Stability Electrochromic Electrodes

Abstract: Nanoparticles of a Prussian blue (PB) analogue, copper hexacyanoferrate, were synthesized by using ultrasonic radiation and characterized by spectroscopic and electrochemical techniques. The nanoparticles (ca. 10 nm diameter) were immobilized onto transparent indium tin oxide electrodes by electrostatic layer-by-layer deposition. These modified electrodes showed interesting electrochromic properties, changing the coloration during the redox process from brown to orange when oxidized. The nanostructured electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 32 publications
4
44
0
1
Order By: Relevance
“…This method can be extended for both nanoparticles and charged biomolecules immobilization. Assemblies between nanoparticles and charged polymers were also reported in literature, for SiO 2 nanoparticles and poly(diallyldimethylammonium chloride) (PDDA), 106 Prussian blue nanoparticles 107 and analogues 108,109 and nickel hydroxide nanoparticles. 110,111 Multilayer films of GOx/AuNPs on Au electrode surface using cysteamine as covalent attachment crosslinker, prepared by LbL technique, was performed by Yang et al 112 Bioelectrocatalytic response was directly correlated to the number of deposited bilayers, due to the amount of active enzyme immobilized on the Au surface.…”
Section: Redox Protein Biosensors Designed With Aunpsmentioning
confidence: 70%
“…This method can be extended for both nanoparticles and charged biomolecules immobilization. Assemblies between nanoparticles and charged polymers were also reported in literature, for SiO 2 nanoparticles and poly(diallyldimethylammonium chloride) (PDDA), 106 Prussian blue nanoparticles 107 and analogues 108,109 and nickel hydroxide nanoparticles. 110,111 Multilayer films of GOx/AuNPs on Au electrode surface using cysteamine as covalent attachment crosslinker, prepared by LbL technique, was performed by Yang et al 112 Bioelectrocatalytic response was directly correlated to the number of deposited bilayers, due to the amount of active enzyme immobilized on the Au surface.…”
Section: Redox Protein Biosensors Designed With Aunpsmentioning
confidence: 70%
“…Recently, Baioni et al 40 reported the synthesis of copper hexacyanoferrate nanoparticles, a Prussian blue derivative, by employing ultrasound radiation. Prussian blue analogues are of great interest, because it is well known that PB lack electroactivity in Na + media.…”
Section: Layer-by-layer Depositionmentioning
confidence: 99%
“…Besides, it turns more significant according to the decrease in the concave or convex surface size. Aurlier publication using spherical nanoparticles showed that the electrochemical response obtained when nanoparticles replace bulk compounds as mediator in biosensors 46,47 or in electrochemical devices 48 is improved. As stated before, the improvement is related not only to the exposition of more active sites available due to the larger surface area but also to the high chemical potential presented by these atoms.…”
Section: Discussionmentioning
confidence: 99%